Enace’s Work, the Epilogue of the Social Housing Built by the State - Haymes-López, Franco Valentino (Universidad de Lima. Carrera de Arquitectura, 2017)
The social housing built by the Government has been a fundamental issue for creating the theoretical body of architecture and urbanism in Peru. However, the studies made seem to avoid the period when the State had the lead role in the planning, realization and promotion of the low cost housing. We refer to the work built by the State building company (Enace) during the 80’s, especially to the work done during its first five years, during the second administration of president Belaunde. Understanding its origins, the tools created to favor the construction of social housing and its finance, thetypological variety, its production scale, as well as the impact of its projects in the city of Lima are issues to be analyzed.